Ambient fine particulate matter induce toxicity in lung epithelial-endothelial co-culture models. (February 2019) - Wang, Guanghe; Zhang, Xiaofeng; Liu, Xinyan; Zheng, Jing; Chen, Renjie; Kan, Haidong
Highlights: A novel approach was used to allow epithelial cells differentiation at ALI condition to mimic the situation in vivo as closely as possible. TEM results showed that particles could pass through the epithelial barrier into the endothelium. Biological adverse effects elicited by PM2.5 were stronger in the tri-culture than in the bi-culture system. Abstract: Epidemiological and toxicological studies have reported that ambient fine particulate matter (PM2.5 ) exposure are linked to adverse effects of cardiopulmonary system. An in vitro suitable model that assesses the interaction among various cell types should be developed to explain the toxic mechanisms occurred in cardiopulmonary system. The Transwell culture method was used to establish bi-culture consisting of A549 alveolar epithelial cells monoculture in apical chamber and EA.hy926 endothelial cells in the basolateral chamber, while tri-culture systems consisting of co-culture (A549 cells and THP-1 differentiated macrophages) in the apical chamber and also EA.hy926 endothelial cells in the basolateral chamber. Ambient PM2.5 collecting from Shanghai city in China was used for experiments. Our results showed that apical exposure of co-cultured cells to PM2.5 (20, 60, 180 μg/ml) for 24 h elicited stronger inflammatory responses than apical exposure of monocultured A549. Endothelial function was assessed via detecting gene expression in EA.hy926 cells, exposure of co-cultured cells induced more vigorous ICAM-1 and caveolin-1 mRNA expression in the tri-culture model than monocultured cells at the same dose of PM2.5 in the bi-culture model. Particles uptake were observed in both epithelial cells and endothelial cells according to TEM images. In conclusion, PM2.5 were able to pass through epithelial barrier and deposited in endothelium to further induce direct effect on endothelium function. The tri-culture system was more realistic and sensitive model to evaluate the impact of particles on the cardiopulmonary system than the bi-culture system. Therefore, the tri-culture system will contribute to explaining of the relationships between PM2.5 and cardiopulmonary diseases.